1998
DOI: 10.1071/pp97084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high temperature during grain filling on starch synthesis in the developing barley grain

Abstract: Plants of malting barley variety Schooner were exposed to 5 days of high temperatures (up to 35°C) during mid grain filling under controlled environment conditions. Grains from heat treated plants accumulated c. 30% less starch than grains from control plants (21/16°C; 14 h day). Reduced starch deposition was not limited by assimilate levels in heat treated grains, but high temperature reduced the conversion of sucrose to starch. The reduction in starch synthesis appeared to result from the effects of diminish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 33 publications
3
50
1
1
Order By: Relevance
“…MacLeod and Duffus 17 reported that the supply of sucrose for starch synthesis may be increased under elevated temperatures in barley, the contradiction between sink and source may inhibit conversion of sucrose to starch, which may be associated with reduced activity of one or several starch synthesis enzymes 31 . Those changes might directly influence A-and B-granule formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MacLeod and Duffus 17 reported that the supply of sucrose for starch synthesis may be increased under elevated temperatures in barley, the contradiction between sink and source may inhibit conversion of sucrose to starch, which may be associated with reduced activity of one or several starch synthesis enzymes 31 . Those changes might directly influence A-and B-granule formation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, high temperatures during grain filling have been reported to severely affect starch and protein accumulation in grains 31 . Starch accounts for approximately 70% of grain weight, and mature endosperms of barley grains generally consist of two distinct starch granules, large, lenticular A-granules and small, spherical Bgranules.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in starch content can be attributed to the reduced enzymic activity associated with the synthesis of amylose and amylopectin. Wallwork et al (1998b) reported that high temperatures (>35°C) resulted in a reduced activity of the granule-bound starch synthase that is responsible for the synthesis of amylose and causes an immediate loss of activity for soluble starch synthase, which is involved in the synthesis of amylopectin. Izydorczyk et al (2001) showed that growing environment had a significant (P ≤ 0.05) effect on amylopectin and amylose content and subsequent biochemical changes during germination.…”
Section: Genotype and Environmental Interactions And Malting Quality mentioning
confidence: 99%
“…Supply of assimilates is never the limiting factor rather its utilization within the grain is the controlling factor of sink activity (Cheikh and Jones 1995;Wallwork et al 1998). Sucrose upon entering into the grain is metabolized by invertases, sucrose synthases and sucrosephosphate synthase (Ho 1988;Yang et al 2004).…”
Section: Introductionmentioning
confidence: 99%